Müller Cell Regulated Microglial Activation and Migration in Rats With N-Methyl-N-Nitrosourea-Induced Retinal Degeneration - Zhang, Shuai; Zhang, Shanshan; Gong, Wenqing; Zhu, Guopei; Wang, Songtao; Wang, Yalin; Halim, Michael; Wang, Kaidi; Zhou, Guomin; Liu, Qiong (Frontiers in Neuroscience, 2018)
ABSTRACT During the pathogenesis of retinitis pigmentosa (RP), the roles of retinal microglia cells after activation have not been totally elucidated. Herein, experimental RP was induced in SD rats by the intraperitoneal injection of N-methyl-N-nitrosourea (MNU) at 50mg/kg. The effects of MNU on retinas were evaluated respectively by retinal histology and electroretinography (ERG) recordings at serial time points. The time-dependent and gradual loss of photoreceptor cells and disrupted arrangement of the outer nuclear layer (ONL) and significant reductions in both a-wave and b-wave amplitudes were observed. Morphology change of retinal microglia cells was found; meanwhile, as the time, the number of Iba1-positive microglia and their infiltration into the ONL gradually increased. Furthermore, physical interaction of microglia-Müller cell processes following microglia activation was determined after MNU injection. In addition, Müller cells increased CX3CL1 secretion, enhanced microglia cells migration, and promoted the latter’s EMT. Our observations implied that during the pathogenesis of RP by MNU, microglia cell presented prominent morphology change, Müller cells can recruit activated microglia infiltration through increasing the secretion of chemotaxis factor CX3CL1 and promoting EMT of retinal microglia cells. This is a novel finding until now, highlighting a potential therapeutic target aimed at regulating the responses.